The Forgotten : tentative de réappropriation aborigène de l’histoire australienne - Virginie BERNARD (E-REA)
The official Australian national history leaves little room for Aboriginal people. Convicts, settlers, gold-diggers, bushrangers and white soldiers are the protagonists of this national history and the Aborigines’ presence is mentioned to emphasize these heroes’ patriotism, “mateship”, bravery, tenacity and initiative. These omissions, both intentional and unintentional, draw a veil over the disturbing histories that challenge the glorious and federative values around which the Australian nation builds itself. The dispossession, massacre, oppression and exploitation of Aboriginal peoples are thus silenced. Nevertheless, collective forgetting cannot permanently stifle subversive voices. In recent decades, many historians and anthropologists have dedicated their research to such repressed histories, provoking virulent reactions among conservative scholars and politicians opposed to a rewriting of history which questions the Australian national narrative and identity. This re-visitation of history is of vital interest to Aboriginal peoples, among them voices who are endeavouring to reclaim Australian history. I propose to illustrate their efforts through a study of The Forgotten, an Aboriginal short film dedicated to the recognition of the Aboriginal soldiers who fought for Australia, only to be forgotten.